2011
DOI: 10.1016/s0034-7094(11)70072-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Minimally Invasive Uncalibrated Cardiac Output Monitor in Patients Undergoing Cesarean Section under Spinal Anesthesia: Report of Four Cases

Abstract: Although this monitor had not been calibrated, it showed a tendency for consistent hemodynamic data in obstetric patients and it may be used as a therapeutic guide or experimental tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…The present data suggest that the LiDCO rapid system may be useful to guide individualized fluid therapy in parturient women. It has been widely reported that, compared with the gold standard for CO measurement, that is, the thermodilution technique, the LiDCO system is able to provide reliable hemodynamic parameters in healthy parturient women undergoing spinal anesthesia, and in high risk parturient women with severe pre‐eclampsia . The benefits of the LiDCO rapid system under spinal anesthesia have been further validated by the rapid detection of intraoperative hemodynamic changes in the present study.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The present data suggest that the LiDCO rapid system may be useful to guide individualized fluid therapy in parturient women. It has been widely reported that, compared with the gold standard for CO measurement, that is, the thermodilution technique, the LiDCO system is able to provide reliable hemodynamic parameters in healthy parturient women undergoing spinal anesthesia, and in high risk parturient women with severe pre‐eclampsia . The benefits of the LiDCO rapid system under spinal anesthesia have been further validated by the rapid detection of intraoperative hemodynamic changes in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, GDFT was reported to stabilize perioperative hemodynamics and reduce the incidence of postoperative complications in high‐risk patients or high‐risk surgical procedures . Stroke volume variation and increase in stroke volume (∆SV) are two indices that are targeted in order to achieve SV optimization for maintaining the plateau of the Frank–Starling curve, which is the fundamental theory of the LiDCO system . Previous studies have assessed the impact of different regimens in preventing spinal anesthesia‐induced hypotension, and it was found that colloid preload, crystalloid and colloid co‐load were more effective than crystalloid preload alone .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high doses of local anesthetics, other factors may contribute to a higher incidence of arterial hypotension [15][16][17][18] , such adrenoceptors in the dorsal horn of the spinal cord. This effect seems to be more intense during pregnancy 4,5,7,8,22,[26][27][28] .…”
Section: Use Of Different Doses Of Hyperbaric Bupivacaine Associated mentioning
confidence: 99%
“…The PulseCO algorithm that was used in analysis of arterial pressure curve by LiDCORapid monitor, has been validated and used in healthy, pregnant patients receiving spinal anaesthesia. (66,67) The absolute value of CI measured with this method has been controversial, however its value for monitoring the trends in CI values has been validated and accepted, also in spinal anaesthesia. (30,63,68) We were aware of the limitations of the method used in the assessment of absolute values of CI; also in SVRI calculations the mean atrial pressure was not measured but arbitrarily set to 7 mmHg.…”
Section: Discussionmentioning
confidence: 99%